Multiple-transportable carbohydrate effect on long-distance triathlon performance - Rowlands, D. S.; Houltham, S. D. (Medicine & Science in Sports & Exercise, 2017)
The ingestion of multiple (2:1 glucose-fructose) transportable carbohydrate in beverages at high rates (>78 g·h) during endurance exercise enhances exogenous carbohydrate oxidation, fluid absorption, gut comfort, and performance relative to glucose alone. However, during long-distance endurance competition, athletes prefer a solid-gel-drink format, and the effect size of multiple-transportable carbohydrate is unknown.